Skill-biased technological change, endogenous labor supply, and the skill premium - Michael Knoblach (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2019)
The evolution of the U.S. skill premium over the past century has been characterized by a U-shaped pattern. The previous literature has attributed this observation mainly to the existence of exogenous, unexpected technological shocks or changes in institutional factors. In contrast, this paper demonstrates that a U-shaped evolution of the skill premium can also be obtained using a simple two-sector growth model that comprises both variants of skill-biased technological change (SBTC): technological change (TC) that is favorable to high-skilled labor and capital-skill complementarity (CSC). Within this framework, we derive the conditions necessary to achieve a non-monotonic evolution of relative wages and analyze the dynamics of such a case. We show that in the short run for various parameter constellations an educational, a relative substitutability, and a factor intensity effect can induce a decrease in the skill premium despite moderate growth in the relative productivity of high-skilled labor. In the long run, as the difference in labor productivity increases, the skill premium also rises. To underpin our theoretical results, we conduct a comprehensive simulation study.
urn:nbn:de:bsz:14-qucosa2-344199
Keywords: E24; J24; J31; O33; O41; 330; Skill-Augmenting Technological Change; Capital-Skill Complementarity; Skill Premium; Neoclassical Growth Model